Gambaran Self-Esteem Siswa dari Keluarga Broken Home dan Implikasinya dalam Pelayanan - Ananda, Putri; Nurfarhanah, Nurfarhanah (TSAQOFAH, 2025)
This study is motivated by the high number of adolescents experiencing low self-esteem, with one of the main contributing factors being an unstable family environment or broken home. The research aims to describe the self-esteem of students from broken home families at SMK Negeri 2 Bukittinggi, based on five key aspects: (1) overall self-esteem, (2) significance, (3) competence, (4) virtue, and (5) power. A quantitative descriptive method was employed, with a sample of 144 students selected using purposive sampling. Data were collected using a self-esteem questionnaire and analyzed through descriptive statistical techniques. The results indicate that: (1) overall self-esteem falls into the low category, (2) the aspects of significance and competence are in the moderate category, and (3) the aspects of virtue and power are in the low category. These findings suggest that students from broken home families tend to have weak self-confidence and self-perception, particularly regarding personal virtue and strength. The study implies that Guidance and Counseling (BK) teachers play a vital role in providing personal development services through individual counseling, group guidance, information services, and classroom guidance to holistically enhance students' self-esteem.